An Analytical Study of the Effectiveness of the Child Development Scheme in Anganwadi Centers of Rudraprayag District - Umesh Chandra (International Journal of Children, 2026)
From the perspective of human development, childhood is regarded as a highly sensitive and multidimensional phase that plays a pivotal role in shaping the trajectory of human life. During childhood, children undergo rapid growth across their mental, social, psychological, and physical domains. Currently, the mental, physical, and social well-being—as well as the overall health—of children remains a grave challenge for the entire world. An increase in nutritional and health-related problems among children is being observed during the COVID-19 pandemic. According to the World Health Organization, more than 264 million children worldwide are grappling with hunger, malnutrition, depression, obesity, underweight conditions, wasting, stunting, and deficiencies in essential vitamins and minerals. Consequently, this situation has led to adverse socio-economic and educational impacts, as well as a noticeable lack of awareness regarding hygiene and sanitation. In the years 2021–2022, approximately 390 million adults aged 18 and above worldwide were found to be underweight. The present study constitutes an analytical examination of the effectiveness of the Child Development Scheme within the Anganwadi centers of the Rudraprayag district, located in the state of Uttrakhand. The primary objective of this research is to assess the effectiveness of various child development interventions—such as supplementary nutrition, counseling, health and nutrition services, immunization, health check-ups, and non-formal pre-school education—across all development blocks of the Rudraprayag district.
Keywords: Anganwadi; ECCE; ICDS; balvatika scheme; child malnutrition